2016
DOI: 10.3390/ijms17101690
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Genome and Gene Expression Changes in Newly Induced Autopolyploid Chrysanthemum lavandulifolium (Fisch. ex Trautv.) Makino

Abstract: Autopolyploidy is widespread in higher plants and plays an important role in the process of evolution. The present study successfully induced autotetraploidys from Chrysanthemum lavandulifolium by colchicine. The plant morphology, genomic, transcriptomic, and epigenetic changes between tetraploid and diploid plants were investigated. Ligulate flower, tubular flower and leaves of tetraploid plants were greater than those of the diploid plants. Compared with diploid plants, the genome changed as a consequence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 62 publications
4
19
0
1
Order By: Relevance
“…epigenetic remodeling to silence parts of the duplicated genome), leading to recombination of the genome and regulatory networks [10,35]. Compared with that of 2nRCC, the methylation level of the Sox9a-Amh-Cyp19a1a regulatory cascade increased in 4nRCC after genome duplication, and a similar result was found previously in the autopolyploid Chrysanthemum lavandulifolium [6]. Meanwhile, the genomic alterations in the promoter region of target genes led to insertions and deletions of CpG sites after an autopolyploidization event, producing an important effect on the genomic methylation status.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…epigenetic remodeling to silence parts of the duplicated genome), leading to recombination of the genome and regulatory networks [10,35]. Compared with that of 2nRCC, the methylation level of the Sox9a-Amh-Cyp19a1a regulatory cascade increased in 4nRCC after genome duplication, and a similar result was found previously in the autopolyploid Chrysanthemum lavandulifolium [6]. Meanwhile, the genomic alterations in the promoter region of target genes led to insertions and deletions of CpG sites after an autopolyploidization event, producing an important effect on the genomic methylation status.…”
Section: Discussionsupporting
confidence: 79%
“…Fertile polyploids play important roles in promoting the exchange of genetic material among species, enriching species diversity, and laying foundations for polyploid breeding [1][2][3][4]. Polyploidy can be classified into autopolyploidy and allopolyploidy [5,6]. The former can be produced by the whole genome duplication (WGD) of a species (autopolyploidization), whereas the latter refers to the merging of genomes from different species after hybridization (allopolyploidization) [7].…”
Section: Introductionmentioning
confidence: 99%
“…The induction of polyploids has been widely used as a strategy to investigate the effects of artificial genomic duplication on several plant species. Morphological, histological, physiological, agronomic, and genomic traits have been evaluated in different studies (Adams and Wendel, 2005;Buggs et al, 2008;Rêgo et al, 2011;Hegarty et al, 2013;Gomes et al, 2014;Tavan et al, 2015;Gao et al, 2016;Iannicelli et al, 2016;Yan et al, 2016;Sadat-Noori et al, 2017;Salma et al, 2017;Zhou et al, 2017). Although polyploidy induction has been widely recognized as an important strategy for chromosome duplication in plants, the protocols are still associated with low efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The leaf growth is a dynamic process often involving independent pathways that direct the cell components (Gao et al, 2016). Previous studies have shown that autotetraploids of Lolium species had long leaves due to the increase in cell length and a faster rate of cell elongation (Sugiyama, 2005).…”
Section: Discussionmentioning
confidence: 99%